Perbedaan Metode Buzz Group Discussion dengan Ceramah Audiovisual terhadap Tingkat Pendidikan Warga Binaan tentang HIV/AIDS di Lembaga Pemasyarakatan Klas IIA Kabupaten Jember (The Differences between Using Buzz Group Discussion Method and Audiovisual Lec - Jihadiah Nur Ikromah; Nurfika Asmaningrum; Lantin Sulistyorini (Pustaka Kesehatan, 2015)
HIV/AIDS increased not only occurred in general population, but also in prison population. Knowledge about HIV/AIDS is urgently needed to prevent the transmission of the disease. This research aimed to determine the differences about Buzz group discussion method and Audiovisual lectures to the knowledge level of inmates about HIV/AIDS in prison class IIA Jember Regency. The research used quasi-experimental with non-equivalent control group pretest-posttest design. Sampling technique used purposive sampling involving 44 respondents divided into intervention group and control group. Data were collected using pretest and postest questionnaires.Data were analyzed by using Wilcoxon test and Mann Whitney test. The result of Wilcoxon test showed that there were differences of knowledge level of inmates about HIV/AIDS before and after health education using buzz group discussion method (p value=0,000) and audiovisual lectures (p value = 0,004). However, there was no difference between intervention group and control group against the knowledge level of inmates about HIV/AIDS (p value=0,337, α=0.05). Buzz group discussion and audiovisual lectures methode can be used as alternative health education method because can help participants more active during the procces of health education, health officer in prison Class IIA Jember regency can choose both as health education methods. Keywords: Buzz group discussion, audiovisual lecture, knowledge level, HIV/AIDS